Selection of Alternative Energy Projects to Implement in Agriculture Cooperatives Using AHP Technique - Asvinjaipetch, Nttapong; Sowawattanakul, Phimphorn (Rajapark Journal, 2024)
This research aimed to analyze the criteria and alternative energy projects appropriate for use in agricultural cooperatives. There are 30 samples composed of 10 samples from professionals, 5 samples each from middle, large, and extra-large-sized cooperatives that are suitable for implementing alternative energy projects or already using alternative energy in the cooperative, and 5 samples from non-cooperative farmers. The instrument for collecting data was the AHP process. Data will be analyzed using descriptive statistics and content analysis. The research results were found as follows; 1) Solar energy has the largest importance value percentages overall at 49.00 followed by biogas, wind energy, and hydro energy at 18.63, 17.07, and 15.30 respectively 2) Payback period provides the largest importance value percentages overall at 22.20 following by resources and geometry, sustainable operations, quality of work and project investment at 21.61, 21.52, 18.60 and 16.06 respectively 3) The research suggests that solar energy is the most suitable energy projects for use in agricultural cooperatives, and the payback period is the most important criterion for considering the selection of alternative energy projects.